Kinetic-Ballooning-Limited Pedestals in Spherical Tokamak Plasmas - Parisi, J F; Guttenfelder, W; Nelson, A O; Gaur, R; Kleiner, A; Lampert, M; Avdeeva, G; Berkery, J W; Clauser, C; Curie, M; Diallo, A; Dorland, W; et al. (arXiv.org, 2024)
A theoretical model is presented that for the first time matches experimental measurements of the pedestal width-height Diallo scaling in the low-aspect-ratio high-\(β\) tokamak NSTX. Combining linear gyrokinetics with self-consistent pedestal equilibrium variation, kinetic-ballooning, rather than ideal-ballooning plasma instability, is shown to limit achievable confinement in spherical tokamak pedestals. Simulations are used to find the novel Gyrokinetic Critical Pedestal constraint, which determines the steepest pressure profile a pedestal can sustain subject to gyrokinetic instability. Gyrokinetic width-height scaling expressions for NSTX pedestals with varying density and temperature profiles are obtained. These scalings for spherical tokamaks depart significantly from that of conventional aspect ratio tokamaks.